A REVIEW OF VISION-BASED PERCEPTIVE INTERFACES: MOUSE ALTERNATIVE APPROACHES - Tariq, U.; A. Asif, M. D.; Yousaf, M. H.; Hussain, F. (The Nucleus, 2013)
Graphical User Interfaces based on WIMP (Window, Icon, Menu, Pointer) paradigm has been a popular choice of interfaces for many systems and has made Human-Computer interaction simpler and easier. In the past few decades great research efforts have been made to make user friendly Human-Computer Interfaces. The Perceptual User Interfaces aims to focus this new form of HCI (Human Computer Interaction). In this study we describe different Vision Based Perceptive Interfaces that make use of different computer vision techniques for tracking and gesture recognition that may serve as an alternative for outdated mouse. The major focus of the work presented here is on the critical evaluation of different vision-Based interfaces that will give the perceptual ability of vision to computers and will make human-Computer interaction more human friendly interaction. The comparative study and critical evaluation using Human Computer Interaction approaches highlights the strength and weakness of the existing vision-Based interfaces. The emphasis of our research is focused on summarizing the literature by highlighting its limitations and strengths.